A Novel Route towards Bicyclo[1.1.1]pentane Sulfoxides from a Bench-Stable Starting Material - Langer, Lukas S.; Stahlberger, Mareen; Bär, Robin M.; Bräse, Stefan (Synlett, 2023)
Bicyclopentanes (BCPs) are non-classical bioisosteres that have gained a lot of interest in drug discovery as non-conjugated rigid hydrocarbons. There has been substantial progress in the synthesis of carbon- and nitrogen-substituted derivatives using [1.1.1]propellane as a precursor, while sulfur-substituted BCPs are rather underdeveloped. This work investigates a new method for the synthesis of BCP-sulfoxides. Herein, a previously reported bench-stable sodium BCP-sulfinate precursor is converted, using a range of aryl and alkyl magnesium bromides, into unsymmetrical BCP-sulfoxides via a convenient one-pot procedure. Furthermore, the conversion of the obtained sulfoxides into sulfoximines is explored.
Keywords: bicyclo[1.1.1]pentane; sulfoxide; sulfoximine; bioisostere; one-pot; Grignard reagent